Interleukin-6 from Adipose-Derived Stem Cells Promotes Tissue Repair by the Increase of Cell Proliferation and Hair Follicles in Ischemia/Reperfusion-Treated Skin Flaps - Pu, Chi-Ming; Chen, Ya-Chun; Chen, Yu-Chen; Lee, Tzu-Lin; Peng, Yu-Sen; Chen, Shun-Hua; Yen, Yu-Hsiu; Chien, Chung-Liang; Hsieh, Jung-Hsien; Chen, Yuh-Lien (Mediators of Inflammation, 2019)
The most common postoperative complication after reconstructive surgery is flap necrosis. Adipose-derived stem cells (ADSCs) and their secretomes are reported to mediate skin repair. This study was designed to investigate whether conditioned media from ADSCs (ADSC-CM) protects ischemia/reperfusion- (I/R-) induced injury in skin flaps by promoting cell proliferation and increasing the number of hair follicles. The mouse flap model of ischemia was ligating the long thoracic vessels for 3 h, followed by blood reperfusion. ADSC-CM was administered to the flaps, and their survival was observed on postoperative day 5. ADSC-CM treatment led to a significant increase in cell proliferation and the number of hair follicles. IL-6 levels in the lysate and CM from ADSCs were significantly higher than those from Hs68 fibroblasts. Furthermore, a strong decrease in cell proliferation and the number of hair follicles was observed after treatment with IL-6-neutralizing antibodies or si-IL-6-ADSC. In addition, ADSC transplantation increased flap repair, cell proliferation, and hair follicle number in I/R injury of IL-6-knockout mice. In conclusion, IL-6 secreted from ADSCs promotes the survival of I/R-induced flaps by increasing cell proliferation and the number of hair follicles. ADSCs represent a promising therapy for preventing skin flap necrosis following reconstructive and plastic surgery.